2008
DOI: 10.31729/jnma.157
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Writing Skills of Pre-Clinical Medical and Dental Undergraduate Students

Abstract: Objective of this prospective study was to assess the acquisition of prescribing skill of preclinicalmedical and dental undergraduate students. Prescription writing skills of 258 students of both firstand second year of MBBS and BDS students were analyzed through an objective structured practicalexamination. MBBS student of second year scored 85.01% and 92.82% respectively in physician anddrug related component whereas first year MBBS students scored 89.9% and 83.4%. BDS studentof first year scored 91.96% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 4 publications
2
30
0
Order By: Relevance
“…This observation is in accordance with that observed in the study of eastern Nepal. 8 Al Khaja et al from Bahrain also reported the limited acquisition of prescription writing skill of medical students during their preclerkship period. 7 In a Nigerian study, final year medical students were found to be also deficient in their prescription writing skills.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is in accordance with that observed in the study of eastern Nepal. 8 Al Khaja et al from Bahrain also reported the limited acquisition of prescription writing skill of medical students during their preclerkship period. 7 In a Nigerian study, final year medical students were found to be also deficient in their prescription writing skills.…”
Section: Resultsmentioning
confidence: 99%
“…7 The prescription writing skill of preclinical medical students was reported suboptimal also in a recent study conducted in the eastern Nepal. 8 A regular assessment of medical students on their prescription writing skills during their training has been suggested as a means of minimizing the related errors and enhancing rational prescribing in their future endeavors. 9 There is no any published data on this skill of preclinical undergraduate students of COMS Bharatpur.…”
Section: Introductionmentioning
confidence: 99%
“…These however, can also be implemented in dentistry and include exposing students to clinical environment and training them in prescription writing during undergraduate studies rather than after graduating in internship, 12 as was concluded in a study in Nepal. 13 It is only then that the house officers would be sufficiently trained to implement their knowledge clinically. Helen and Joseph have also reported that with a change in the dental curriculum that focuses more on pharmacology and therapeutics in the preclinical years, significant improvements in the knowledge of dental graduates regarding drug prescribing can be seen.…”
Section: Prescription Writing Skills Surveymentioning
confidence: 99%
“…As in a previous study among medical students , we believe that participants should have high assessment scores (≥80%), which would demonstrate their competence in prescribing drugs safely and effectively. The lack of prescribing competence among dental students and dental‐care providers has also been reported in other countries and is a concern because it may have undesirable consequences for patients, such as adverse drug events and suboptimal treatment . Not surprisingly, dental specialists outperformed the other groups on several aspects of prescribing, possibly because oral and maxillofacial surgeons receive additional CPT education during their training.…”
Section: Discussionmentioning
confidence: 99%